ANALISIS KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN TANGGAMUS - Irianto Loka (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2010)
Human resources is an important factor in the development process. Good Gevernance Theimplementation is a prerequisite for any government to realize the aspirations of the community inachieving the goals and ideals of nation and state.Improved employee performance can not be separated from the leader's responsibility isone of them to motivate people to work better by eliminating bad habits-habits that can degrade theperformance of employees. In this research, leadership and motivation to work together and arepartially affect the performance of employees.